2007
DOI: 10.1091/mbc.e06-11-1040
|View full text |Cite
|
Sign up to set email alerts
|

Cell Polarity Development and Protein Trafficking in Hepatocytes Lacking E-Cadherin/β-Catenin–based Adherens Junctions

Abstract: Using a mutant hepatocyte cell line in which E-cadherin and ␤-catenin are completely depleted from the cell surface, and, consequently, fail to form adherens junctions, we have investigated adherens junction requirement for apical-basolateral polarity development and polarized membrane trafficking. It is shown that these hepatocytes retain the capacity to form functional tight junctions, develop full apical-basolateral cell polarity, and assemble a subapical cortical F-actin network, although with a noted dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 35 publications
(45 reference statements)
5
51
0
Order By: Relevance
“…Furthermore we also silenced E-cadherin expression in RCC10 cells and observed no effect on TJ assembly (Figure 3). Taken together this implies that disruption of TJs is not dependent on E-cadherin down-regulation in these cells and is consistent with other reports showing that AJ assembly in some other settings is not a prerequisite for TJ formation (Potempa and Ridley, 1998;Chen et al, 2000;Theard et al, 2007). Notably we found that VHL status had a marked effect on expression of occludin and claudin 1, which involved up-regulation at the mRNA level.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore we also silenced E-cadherin expression in RCC10 cells and observed no effect on TJ assembly (Figure 3). Taken together this implies that disruption of TJs is not dependent on E-cadherin down-regulation in these cells and is consistent with other reports showing that AJ assembly in some other settings is not a prerequisite for TJ formation (Potempa and Ridley, 1998;Chen et al, 2000;Theard et al, 2007). Notably we found that VHL status had a marked effect on expression of occludin and claudin 1, which involved up-regulation at the mRNA level.…”
Section: Discussionsupporting
confidence: 92%
“…8). Tight junction functionality was not affected by E-cadherin depletion (Capaldo and Macara, 2007;Theard et al, 2007). Thus, we speculate that the inhibition of actomyosin contraction might have two mainly non-exclusive effects.…”
Section: Discussionmentioning
confidence: 80%
“…Also, HepG2 cells expressing p27S10A develop full apical-basolateral cell polarity, although with a delay and without subsequent apical lumen remodelling (Théard et al, 2007). It is possible that additional adhesion proteins have compensated for the loss of E-cadherin and ␤-catenin at the cell surface, as was suggested in the conditional E-cadherin knockout mice (Battle et al, 2006).…”
Section: Discussionmentioning
confidence: 92%